Strange diffusion - Balescu, R. (Condensed Matter Physics, 1998)
Strange diffusion is deﬁned as a process in which the mean square displacement of a randomly walking test particle behaves asymptotically as x²(t) ~ tα , with α ≠ 1 . A brief review of the properties of such processes is presented, stressing their deep difference from the corresponding normal diffusive evolution. A number of examples are discussed, including diffusion of charged particles in a ﬂuctuating magnetic ﬁeld, continuous time random walks and transport in chaotic Hamiltonian systems.